UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN INSULIN (Smallanthussonchifolius) TERHADAP BAKTERI Bacillus cereus - Kesaktian Manurung; Ahmad Ghazali; Ulfayani Mayasari (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Insulin leaves are known as one of the ingredients of traditional medicine. Insulin leaves contain potential substances such as tannins, alkaloids, flavonoids, saponins, and terpenoids which have antibacterial abilities. This study aims to determine the effectiveness of insulin leaf ethanol extract as an antibacterial. This research is an experimental study that includes the collection and processing of insulin leaf samples, examination of the characteristics of Simplisia, phytochemical screening, testing of the antibacterial diffusion method using a disk paper brace, and using the One Way ANOVA analysis method. The test results showed that the ethanol extract could inhibit bacterial growth at a concentration of 50 - 60% with an average resistor potential of 14.8 - 17.83 mm while Ampicillin as a comparison control averaged 33.62 mm. So that the ethanol extract of insulin leaves was effective in inhibiting the growth of Bacillus cereus bacteria with a minimum resistance concentration of 60 mg/ml. Keywords: Antibacterial, Bacillus cereus, insulin leaf extract